Asset Management with Trading Uncertainty - Foley, Duncan K.; Hellwig, Martin F. (Review of Economic Studies, 1975)
Duncan K. Foley, Martin F. Hellwig; Asset Management with Trading Uncertainty12, The Review of Economic Studies, Volume 42, Issue 3, 1 July 1975, Pages 327